Effects of victim’s body posture and attacker’s gender on slashing attacks: a biomechanical study - Li, Shangxiao; Yuan, Shufang; Shi, Yi; Ni, Bin; Guo, Wenxia; Yang, Chaopeng; Wang, Mingzhi; Hao, Weiya (Frontiers in Bioengineering and Biotechnology, 2024)
Objective: The purpose of this study was to evaluate the biomechanical characteristics for males and females when using a Chinese kitchen knife to slash the neck of a dummy while it was in standing and supine positions. Methods: A total of 12 male and 12 female college students participated in this study. Kinematic, kinetic and surface electromyography (sEMG) data were evaluated when slashing a dummy’s neck while it was in standing and supine positions using a Chinese kitchen knife. Results: When slashing the neck of a standing dummy, participants showed shorter contact time (19.5%) and slower shoulder velocities (30.9%) as well as higher hip velocity (26.0%) and root mean square (RMS) and integral electromyography (iEMG) for the anterior deltoid (51.3% and 51.2%, respectively) compared to those while the dummy is in supine position (all p < 0.05), regardless of gender. When slashing a dummy’s neck while it was in standing and supine positions, male participants showed higher shoulder, elbow and wrist velocities (22.6%, 22.7% and 24.4%, respectively) as well as higher slashing velocity (19.8%), slashing force (24.2%) and energy (46.2%) compared to female participants (all p < 0.05). In addition, male participants showed shorter contact time (17.8%), and the values of RMS as well as iEMG of the anterior deltoid, biceps brachii, extensor carpi radialis longus, flexor carpi ulnaris was less than female participants (98.9%, 47.3%, 65.6% and 33.4% for RMS, 115.1%, 59.4%, 80.1% and 47.8% for iEMG, respectively). Conclusion: There was no difference in slashing speed, slashing force and energy when using a Chinese kitchen knife to slash the dummy’s neck while it was in different body postures (standing and supine), suggesting similar level of injury severity. However, there were significant differences in slashing action patterns between the two body postures, with longer contact time, smaller hip velocity, greater shoulder velocity, and less muscle activation level of the deltoid exertion when slashing the dummy’s neck in the supine position. Gender may have a greater effect on the severity of slashing, and gender difference may be partly related to the body weight difference.